Strategi Komunikasi Humas PT KCI Dalam Program CSR Pojok Baca di Stasiun Jakarta Kota - Putriana, Muria; Sari, Wina Puspita; Sitorus, Putri Yohana; Kurnia, Salsabila; Candra, Ghina Salsabila; Paramita, Theresia Resa; Budiono, Riyaan; Fauzan, Nugraha Robby (JIKA (Jurnal Ilmu Komunikasi Andalan), 2024)
The aim of this research is to identify the public relations strategies of PT KAI in communicating the CSR program "Pojok Baca" to its users. Corporate Social Responsibility (CSR) Pojok Baca at Jakarta Kota Station conducted by PT KAI is the result of cooperation between Gramedia and Kompasiana as an effort to create a culture of reading interest and build a good relationship between the company and the community. To launch this CSR Reading Corner activity, good communication is needed to the community, therefore this study aims to find out the communication strategy of PT KAI's public relations in communicating the CSR Reading Corner programme to its users. This type of research is descriptive qualitative. Data validity uses triangulation techniques. Based on the results of the study, it is known that the public relations communication strategy carried out by PT KAI uses media and online-based communication methods and releases in the public relations index, such as Instagram, Twitter, and inviting the media to cover activities. Keywords: Public Relations; Corporate Social Responsibility; Public Relations Communication; Communication Strategy